2007
DOI: 10.1111/j.1748-0361.2007.00096.x
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Colorectal Screening in Rural Colorado: Testing to Prevent Colon Cancer in the High Plains Research Network

Abstract: This study suggests that health care providers should be vigilant in counseling their patients 50 and older to have a colorectal cancer test. Community programs designed to promote colon cancer screening should encourage residents to have regular contact with their primary care physician and ask their doctor for a screening test. Additionally, programs should provide financial assistance for testing for low-income and uninsured patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1
3

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 11 publications
3
38
1
3
Order By: Relevance
“…Although this is similar to what may happen in quality improvement work, it seems to go beyond the purpose and gains measured in many studies that are limited to the specific study topic. 22,23,31,32,39 Providing practices the tools and motivation to move to the next step has been the purported purpose of "quality collaboratives," but few have been shown to achieve that goal. [52][53][54] Understanding the importance of systems of care and system support is the initial step in many facilitated models of practice improvement.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this is similar to what may happen in quality improvement work, it seems to go beyond the purpose and gains measured in many studies that are limited to the specific study topic. 22,23,31,32,39 Providing practices the tools and motivation to move to the next step has been the purported purpose of "quality collaboratives," but few have been shown to achieve that goal. [52][53][54] Understanding the importance of systems of care and system support is the initial step in many facilitated models of practice improvement.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33][34][35][36][37][38][39] Few studies have addressed potential benefits for the practice that extend beyond the study topic. As PBRN studies move from simply recording events to evaluating new management strategies and systems, the potential benefits to the practices increase.…”
mentioning
confidence: 99%
“…CRC usually develops from precancerous polyps in the colon or rectum, which can be found with screening, and they can be removed before they turn into cancer [2]. Previous studies on determinants of participation in fecal occult blood test (FOBT) based screening have indicated that female gender [3], high education [4,5], high social status [6], and marriage [5,7] increase the probability of CRC screening participation.…”
Section: Original Articlementioning
confidence: 99%
“…The survey instrument incorporated questions adapted from the Eastern Colorado Colon Cancer Questionnaire, 11,12 which is a telephone scripted survey used to collect baseline colon cancer screening data from the HPRN catchment area. The Health Belief Model 13 was used as the conceptual model for questions that addressed patient knowledge, attitudes, and beliefs regarding screening for CRC.…”
Section: Survey Developmentmentioning
confidence: 99%
“…A previous study reported on the CRC screening attitudes and behaviors of a random sample of community members in rural Colorado. 11 Our study assessed the screening attitudes and behaviors of patients in those same communities attending primary care practices that are part of a practice-based research network (PBRN) in rural Colorado. Knowing what happens once patients access care can provide valuable information about patient and provider beliefs and behaviors that affect CRC screening.…”
Section: Introductionmentioning
confidence: 99%